THE RELATIONSHIP OF GESTURES AND QUANTIFICATION OF LANGUAGE PHENOMENA IN CZECHPERSONS WITH APHASIA - Janečka, Martin (Bohemica Olomucensia, 2022)
In aphasic persons speaking Czech, I verify the following assumption established by Jakob et al. (2011): the more speech-limited an aphasic person is, the more gestures he/she produces during the interpretation of a story.It was found that the number of words produced by aphasic persons varies, partially dependent on the specific type of aphasia. This is particularly true on both ends of the scale - people with large speech distortion use the highest quantity of gestures, people with low speech distortion use gestures to a lesser extent. Within the classification of semantic gestures, I focus particularly on iconic and deictic gestures. In addition, I presume that symbolic gestures (i.e., emblems) do not occur in aphasic persons' speech, because aphasic persons prefer gestures that display the plot in the most concrete way.My data correlate with other studies dealing with this topic - aphasic persons do use gestures intentionally to substitute for their verbal deficiency. At the same time, they mostly use very concrete (iconic) gestures, which enable them to transmit a large volume of information.
Keywords: aphasia; multimodality; gestures; type-token ratio; hapax legomenon